TAFSIR AHKAM DALAM FIQIH NAFKAH; - Habibi Al Amin; Mas Umar (LPPM UNHASY, 2022)
This article is the result of qualitative literature research. The purpose of this research is to explore the establishment of the concept of family maintenance in Islam. The scholarly debate boils down to two categories. First, the salaf scholars mostly agree that family maintenance is in the hands of the husband; second, the opinion of the muta'akhkhirin scholars that maintenance is not absolutely on the husband's shoulders but is flexible, either the husband or the wife depending on the circumstances. This article situates the legal reasoning of both opinions by considering the theory of tafsir ahkam as a tool. The conclusion is nafkah in usul perspective is the obligation of the husband with all the rights and obligations attached to nafkah, but the obligation can change to the wife with the consequent rights and obligations attached to nafkah. Data in this research ara the interpretation of the verses of the Qur'an taken from several books of Quranic interpretation. Keywords: Qur’an exegesis, nafka, career women. Daftar Pustaka Al Amin, Habibi.